EVALUATION OF JEJUNAL POUCH ROUX-EN-Y RECONSTRUCTION AFTER DISTAL GASTRECTOMY - HAYASHIDA, Yuichi; KAMATA, Toru; YOSHIMOTO, Katsuhiro; KANNO, Masahiro; TAJIMA, Hidehiro; ISHII, Kaname; TAKEDA, Toshiya (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2005)
We have employed Roux-en Y reconstruction using a jejunal pouch (pouch RY) as a reconstructive method after distal gastrectomy to prevent stricture at the anastomosis and to improve “symptoms of the excised stomach”, and have observed postoperative clinical courses of those patients. The pouch RY with Billroth-I method (B-I) and the pouch RY are compared for postoperative outcomes and postoperative complaints. Thirty-one cases of B-I and 58 cases of pouch RY were enrolled in this study. A questionnaire survey was conducted to evaluate postoperative complaints of those patients. No significant difference in the incidence of postoperative complications was noted between the pouch RY and B-I groups. Although there was no significant difference in changing rate of postoperative body weight, the outcome of the pouch RY group was favorable. No significant differences were also observed in postoperative complaints asked by the questionnaire survey. It is concluded that the pouch RY bears comparison with B-I and has benefits in terms of the safety and prevention of anastomotic stricture compared with other methods of reconstruction, so that the pouch RY can be one of reconstructive methods after distal gastrectomy.